Comparison of Treatment Options and Loss of Labor and Disability Ratio in Patients with Extremity Fractures - Şenol, Ender; Çelik, Cemil; Ata, Uğur; Meral, Orhan; Özkayın, Nadir (The Bulletin of Legal Medicine, 2019)
Objective: In our study, the success of the treatments applied to the bone fractures resulting from traffic accidents and the disability reports of those cases prepared using “The Scales of Measurement of Disabilities” and "The Scale of Disability Rates”, and the ratios obtained using both scales were compared. Materials and Methods: In our study we evaluated 142 patients with unilateral extremity fractures who were treated at Ege University Faculty of Medicine, Department of Orthopedics and Traumatology between February 01, 2016 and February 01, 2017 and who applied to our department for the evaluation of the sequelae rate. Results:There were significant differences in the sequelae rates after orthopedic plaster-splint, plate-screw and intramedullary needle treatments (p<0.05). It was concluded that there was a strong positive correlation between disability and invalidity rates as a result of fractures, the average invalidity rate was calculated as 15%, the disability rate was calculated as 5.5%, and the difference was found to be statistically significant. Discussion:On compensation account, using “The Scales of Measurement of Disabilities” instead of "The Scale of Disability Rates” due to the lack of professional and age assessment when calculating this ratio, the loss of rights arises.We believe that steps should be taken to create a new regulation that includes age and profession, which includes more objective evaluations for the elimination of this grievance and the calculation of the disability rate.